A Technical and Environmental Study of Fortified Structures Used in Coal Mining in Norte de Santander - Bolívar-León, Rafael; Triviño-Jaimes, Neyl Richard; García-Mogollón, Javier Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The mechanic characterization of fortified structures on coal mining at Norte de Santander and the contribution of this sector to the deforestation have been poorly studied. The loss of forests zones between 1990 and 2010 was about 26%, however, the calculation shows that the coal mining sector contribution is only 0,36%. In total, were determined 17 geometric variables on the structures, but only two of them affect significantly their mechanical performance. A mechanical simulation and a 25experimental design were used to obtain a selection diagram of diameter and angle for the structures, which theoretically ensures a better use of wood. It could be used wood diameters as small as 14 cm, without compromising the mechanical properties of the design, leading to a possible shorter logging time, lower transport cost and easier assembly into the mine.